Understanding the Transnational Character of Money Laundering: The Changing Face of Law Enforcement from Domestic Affairs to the International Cooperation - AMRANI, Hanafi (Journal of Advanced Research in Law and Economics, 2017)
Taking into account the advantages of globalization, money-laundering offences have been increasingly crossing national boundaries and expanding into worldwide operation in the past few decades. In this setting, it is evident that no single country can prevent and control this type of crime in a unilateral action, but rather needs interstate cooperation. Some efforts have been taken by the domestic as well as the international community in order to respond to the problem of cross-border money laundering. The ratifications of international conventions, the expansion of domestic criminal laws and law enforcement beyond national territory, and the establishment of international modalities of cooperation are some evidence of such efforts. However, some obstacles that hinder the effectiveness of conducting international cooperation are inevitable. Three of the factors that affect the effectiveness of interstate cooperation when dealing with transnational character of money laundering include the traditional view of sovereignty, the diversity of national legal systems, and the capability to perform international cooperation.